The Role of Job Satisfaction in Mediating the Effect of Perceived Organizational Support on Intention to Stay Among F&B Industry Employees in Cirebon - Siska Apriyanti; Agi Syarif Hidayat (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the mediating role of job satisfaction in the relationship between perceived organizational support and intention to stay among employees in the Food & Beverage (F&B) industry in Cirebon. The study is motivated by the high turnover rate within the F&B sector, which requires organizations to better understand psychological factors that contribute to employee retention. A quantitative research design was employed using a survey method involving 110 employees selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that perceived organizational support has a positive and significant effect on job satisfaction. Job satisfaction, in turn, significantly influences employees’ intention to stay. Furthermore, perceived organizational support directly affects intention to stay; however, the effect becomes stronger when mediated by job satisfaction. These results confirm that job satisfaction functions as a partial mediator that strengthens the relationship between organizational support and employee retention. Therefore, enhancing organizational support accompanied by strategies aimed at improving job satisfaction is essential for increasing employee loyalty and long-term retention in the F&B industry.